Curriculum Development in Islamic Boarding School - Rizky Ksatria Surya Cakti Ramadhani; Nur Arifah Dzul Qo'dah; Ifa Liyin Azizah; Mohammad Asrori Alfa (Didaktika: Jurnal Kependidikan, 2024)
The development of the curriculum in Islamic boarding schools is currently experiencing significant developments. In the past, the curriculum at Islamic boarding schools only focused on religious issues, and considered learning there to be old-fashioned, but now the development has shifted from traditional revivalism to exploring it by combining several curricula, in this case Islamic boarding schools are responsive to changing times. Therefore, this discussion focuses on curriculum developments that occur in educational institutions around us with increasingly developing conditions, especially in Islamic boarding schools. The research method uses library research or literature study with a descriptive qualitative research approach. Meanwhile, the data collection technique here refers to literature study by analyzing books, research journals, literature notes, internet sites and so on related to the theme being studied. The findings show that the curriculum development process in Islamic boarding schools needs to implement curriculum integration such as that found in the Nurul Ummah Mojokerto modern Islamic boarding school which implements several curricula such as combining the international standard Madrasah Aliyah formal curriculum and the Egyptian Al-Azhar standard Madrasah Diniyah curriculum and the hidden curriculum. such as student extracurricular activities. Curriculum development here still adheres to the principles and goals to be achieved. This is done so that students can determine their interests and talents well. Seeing the very rapid development of the times, educational institutions such as Islamic boarding schools, which are considered ancient institutions, must develop and always improve their curriculum system to be better.